Section	3.2
                  Inverse	Functions	and	Logarithms

                               V63.0121.027, Calculus	I


...
Outline




  Inverse	Functions



  Derivatives	of	Inverse	Functions



  Logarithmic	Functions




                     ...
What	is	an	inverse	function?



   Definition
   Let f be	a	function	with	domain D and	range E. The inverse of f is
   the	...
What	is	an	inverse	function?



   Definition
   Let f be	a	function	with	domain D and	range E. The inverse of f is
   the	...
What	functions	are	invertible?



   In	order	for f−1 to	be	a	function, there	must	be	only	one a in D
   corresponding	to	...
Graphing	an	inverse	function



     The	graph	of f−1
     interchanges	the x and y               f
                      ...
Graphing	an	inverse	function



     The	graph	of f−1
     interchanges	the x and y                f
                     ...
How	to	find	the	inverse	function
 1. Write y = f(x)
 2. Solve	for x in	terms	of y
 3. To	express f−1 as	a	function	of x, in...
How	to	find	the	inverse	function
 1. Write y = f(x)
 2. Solve	for x in	terms	of y
 3. To	express f−1 as	a	function	of x, in...
How	to	find	the	inverse	function
 1. Write y = f(x)
 2. Solve	for x in	terms	of y
 3. To	express f−1 as	a	function	of x, in...
Outline




  Inverse	Functions



  Derivatives	of	Inverse	Functions



  Logarithmic	Functions




                     ...
derivative	of	square	root


                        √                   dy
   Recall	that	if y =       x, we	can	find      ...
Theorem	(The	Inverse	Function	Theorem)
Let f be	differentiable	at a, and f′ (a) ̸= 0. Then f−1 is	defined	in	an
open	interv...
Theorem	(The	Inverse	Function	Theorem)
Let f be	differentiable	at a, and f′ (a) ̸= 0. Then f−1 is	defined	in	an
open	interv...
Outline




  Inverse	Functions



  Derivatives	of	Inverse	Functions



  Logarithmic	Functions




                     ...
Logarithms

  Definition
      The	base a logarithm loga x is	the	inverse	of	the	function ax

                          y =...
Logarithms

  Definition
       The	base a logarithm loga x is	the	inverse	of	the	function ax

                            ...
Logarithms

  Definition
       The	base a logarithm loga x is	the	inverse	of	the	function ax

                            ...
Logarithms

  Definition
        The	base a logarithm loga x is	the	inverse	of	the	function ax

                           ...
Logarithms	convert	products	to	sums

      Suppose y = loga x and y′ = loga x′
                                  ′
      T...
Example
Write	as	a	single	logarithm: 2 ln 4 − ln 3.




                                              .   .   .   .   .   .
Example
Write	as	a	single	logarithm: 2 ln 4 − ln 3.

Solution
                                        42
    2 ln 4 − ln 3...
Example
Write	as	a	single	logarithm: 2 ln 4 − ln 3.

Solution
                                        42
    2 ln 4 − ln 3...
Example
Write	as	a	single	logarithm: 2 ln 4 − ln 3.

Solution
                                        42
    2 ln 4 − ln 3...
“ .
                      . lawn”




        .




.
Image	credit: Selva
                                .   .   .   .   ...
Graphs	of	logarithmic	functions

       y
       .
                    . = 2x
                    y


                    ...
Graphs	of	logarithmic	functions

       y
       .
                    . = 3x= 2x
                    y . y


            ...
Graphs	of	logarithmic	functions

       y
       .
             . = .10x 3x= 2x
             y y=.    y


                ...
Graphs	of	logarithmic	functions

       y
       .
             . = .10=3xx 2x
                  y xy
             y y. = ...
Change	of	base	formula	for	exponentials

   Fact
   If a > 0 and a ̸= 1, then

                                          l...
Change	of	base	formula	for	exponentials

   Fact
   If a > 0 and a ̸= 1, then

                                           ...
Upcoming SlideShare
Loading in …5
×

Lesson 15: Inverse Functions and Logarithms

2,961 views

Published on

The inverse of a function "undoes" the effect of the function. We look at the implications of that property in the derivative, as well as logarithmic functions, which are inverses of exponential functions.

Published in: Education, Technology
0 Comments
0 Likes
Statistics
Notes
  • Be the first to comment

  • Be the first to like this

No Downloads
Views
Total views
2,961
On SlideShare
0
From Embeds
0
Number of Embeds
16
Actions
Shares
0
Downloads
62
Comments
0
Likes
0
Embeds 0
No embeds

No notes for slide

Lesson 15: Inverse Functions and Logarithms

  1. 1. Section 3.2 Inverse Functions and Logarithms V63.0121.027, Calculus I October 22, 2009 Announcements Quiz on §§2.5–2.6 next week Midterm course evaluations at the end of class . . Image credit: Roger Smith . . . . . .
  2. 2. Outline Inverse Functions Derivatives of Inverse Functions Logarithmic Functions . . . . . .
  3. 3. What is an inverse function? Definition Let f be a function with domain D and range E. The inverse of f is the function f−1 defined by: f−1 (b) = a, where a is chosen so that f(a) = b. . . . . . .
  4. 4. What is an inverse function? Definition Let f be a function with domain D and range E. The inverse of f is the function f−1 defined by: f−1 (b) = a, where a is chosen so that f(a) = b. So f−1 (f(x)) = x, f(f−1 (x)) = x . . . . . .
  5. 5. What functions are invertible? In order for f−1 to be a function, there must be only one a in D corresponding to each b in E. Such a function is called one-to-one The graph of such a function passes the horizontal line test: any horizontal line intersects the graph in exactly one point if at all. If f is continuous, then f−1 is continuous. . . . . . .
  6. 6. Graphing an inverse function The graph of f−1 interchanges the x and y f . coordinate of every point on the graph of f . . . . . . .
  7. 7. Graphing an inverse function The graph of f−1 interchanges the x and y f . coordinate of every point on the graph of f .−1 f The result is that to get the graph of f−1 , we . need only reflect the graph of f in the diagonal line y = x. . . . . . .
  8. 8. How to find the inverse function 1. Write y = f(x) 2. Solve for x in terms of y 3. To express f−1 as a function of x, interchange x and y . . . . . .
  9. 9. How to find the inverse function 1. Write y = f(x) 2. Solve for x in terms of y 3. To express f−1 as a function of x, interchange x and y Example Find the inverse function of f(x) = x3 + 1. . . . . . .
  10. 10. How to find the inverse function 1. Write y = f(x) 2. Solve for x in terms of y 3. To express f−1 as a function of x, interchange x and y Example Find the inverse function of f(x) = x3 + 1. Answer √ y = x3 + 1 =⇒ x = 3 y − 1, so √ f−1 (x) = 3 x−1 . . . . . .
  11. 11. Outline Inverse Functions Derivatives of Inverse Functions Logarithmic Functions . . . . . .
  12. 12. derivative of square root √ dy Recall that if y = x, we can find by implicit differentiation: dx √ y= x =⇒ y2 = x dy =⇒ 2y =1 dx dy 1 1 =⇒ = = √ dx 2y 2 x d 2 Notice 2y = y , and y is the inverse of the squaring function. dy . . . . . .
  13. 13. Theorem (The Inverse Function Theorem) Let f be differentiable at a, and f′ (a) ̸= 0. Then f−1 is defined in an open interval containing b = f(a), and 1 (f−1 )′ (b) = ′ −1 f (f (b)) . . . . . .
  14. 14. Theorem (The Inverse Function Theorem) Let f be differentiable at a, and f′ (a) ̸= 0. Then f−1 is defined in an open interval containing b = f(a), and 1 (f−1 )′ (b) = ′ −1 f (f (b)) “Proof”. If y = f−1 (x), then f (y ) = x , So by implicit differentiation dy dy 1 1 f′ (y) = 1 =⇒ = ′ = ′ −1 dx dx f (y) f (f (x)) . . . . . .
  15. 15. Outline Inverse Functions Derivatives of Inverse Functions Logarithmic Functions . . . . . .
  16. 16. Logarithms Definition The base a logarithm loga x is the inverse of the function ax y = loga x ⇐⇒ x = ay The natural logarithm ln x is the inverse of ex . So y = ln x ⇐⇒ x = ey . . . . . . .
  17. 17. Logarithms Definition The base a logarithm loga x is the inverse of the function ax y = loga x ⇐⇒ x = ay The natural logarithm ln x is the inverse of ex . So y = ln x ⇐⇒ x = ey . Facts (i) loga (x · x′ ) = loga x + loga x′ . . . . . .
  18. 18. Logarithms Definition The base a logarithm loga x is the inverse of the function ax y = loga x ⇐⇒ x = ay The natural logarithm ln x is the inverse of ex . So y = ln x ⇐⇒ x = ey . Facts (i) loga (x · x′ ) = loga x + loga x′ (x) (ii) loga ′ = loga x − loga x′ x . . . . . .
  19. 19. Logarithms Definition The base a logarithm loga x is the inverse of the function ax y = loga x ⇐⇒ x = ay The natural logarithm ln x is the inverse of ex . So y = ln x ⇐⇒ x = ey . Facts (i) loga (x · x′ ) = loga x + loga x′ (x) (ii) loga ′ = loga x − loga x′ x (iii) loga (xr ) = r loga x . . . . . .
  20. 20. Logarithms convert products to sums Suppose y = loga x and y′ = loga x′ ′ Then x = ay and x′ = ay ′ ′ So xx′ = ay ay = ay+y Therefore loga (xx′ ) = y + y′ = loga x + loga x′ . . . . . .
  21. 21. Example Write as a single logarithm: 2 ln 4 − ln 3. . . . . . .
  22. 22. Example Write as a single logarithm: 2 ln 4 − ln 3. Solution 42 2 ln 4 − ln 3 = ln 42 − ln 3 = ln 3 ln 42 not ! ln 3 . . . . . .
  23. 23. Example Write as a single logarithm: 2 ln 4 − ln 3. Solution 42 2 ln 4 − ln 3 = ln 42 − ln 3 = ln 3 ln 42 not ! ln 3 Example 3 Write as a single logarithm: ln + 4 ln 2 4 . . . . . .
  24. 24. Example Write as a single logarithm: 2 ln 4 − ln 3. Solution 42 2 ln 4 − ln 3 = ln 42 − ln 3 = ln 3 ln 42 not ! ln 3 Example 3 Write as a single logarithm: ln + 4 ln 2 4 Answer ln 12 . . . . . .
  25. 25. “ . . lawn” . . Image credit: Selva . . . . . .
  26. 26. Graphs of logarithmic functions y . . = 2x y y . = log2 x . . 0 , 1) ( ..1, 0) . ( x . . . . . . .
  27. 27. Graphs of logarithmic functions y . . = 3x= 2x y . y y . = log2 x y . = log3 x . . 0 , 1) ( ..1, 0) . ( x . . . . . . .
  28. 28. Graphs of logarithmic functions y . . = .10x 3x= 2x y y=. y y . = log2 x y . = log3 x . . 0 , 1) ( y . = log10 x ..1, 0) . ( x . . . . . . .
  29. 29. Graphs of logarithmic functions y . . = .10=3xx 2x y xy y y. = .e = y . = log2 x y . = ln x y . = log3 x . . 0 , 1) ( y . = log10 x ..1, 0) . ( x . . . . . . .
  30. 30. Change of base formula for exponentials Fact If a > 0 and a ̸= 1, then ln x loga x = ln a . . . . . .
  31. 31. Change of base formula for exponentials Fact If a > 0 and a ̸= 1, then ln x loga x = ln a Proof. If y = loga x, then x = ay So ln x = ln(ay ) = y ln a Therefore ln x y = loga x = ln a . . . . . .

×